Royal statues in Egypt 300 BC-AD 220 : context and function - Brophy, Elizabeth, 1986- (Archaeopress Egyptology, 2015)
The aim of this work is to approach Ptolemaic and Imperial royal sculpture in Egypt dating between 300 BC and AD 220 (the reigns of Ptolemy I and Caracalla) from a contextual point of view.